Parasites of the Central American tapir Tapirus bairdii (Perissodactyla: Tapiridae) in Chiapas, Mexico - Cruz Aldán, Epigmenio; Lira Torres, Iván; Güiris Andrade, Dario Marcelino; Osorio Sarabia, David; Quintero M., Ma. Teresa (Revista de Biología Tropical, 2006)
We analyzed 19 samples of Baird ́s tapir feces from La Sepultura Biosphere Reserve, collected between March and July 1999. We also took samples directly from a male tapir captured at the Montes Azules Biosphere Reserve. Both reserves are in Chiapas, Mexico. We used five techniques: flotation, MacMaster, micrometric, Ritchie’s sedimentation and Ferreira ́s quantitative. In addition, we collected ectoparasites from animals captured in both reserves and from a captive couple from Tuxtla Gutierrez, Chiapas. These nematodes and protozoans were found: Agriostomun sp., Lacandoria sp., Neomurshidia sp., Trichostrongylus sp., Strongylus sp., Brachylumus sp, and an unidentified species of ancilostomaide. We also found Eimeria sp. and Balantidium coli, as well as the mites Dermacentor halli, Dermacentor latus, Amblyomma cajannense, Amblyomma coelebs, Amblyomma ovale, Anocentor nitens and Ixodes bicornis.